Enhanced Humoral Immune Response After COVID-19 Vaccination in Elderly Kidney Transplant Recipients on Everolimus Versus Mycophenolate Mofetil–containing Immunosuppressive Regimens. Issue 8 (11th May 2022) - de Boer, Silke E.; Berger, Stefan P.; van Leer–Buter, Coretta C.; Kroesen, Bart-Jan; van Baarle, Debbie; Sanders, Jan-Stephan F.; ,
Abstract : Background: Elderly kidney transplant recipients (KTRs) represent almost one third of the total kidney transplant population. These patients have a very high coronavirus disease 2019 (COVID-19)–related mortality, whereas their response to COVID-19 vaccination is impaired. Finding ways to improve the COVID-19 vaccination response in this vulnerable population is of uttermost importance. Methods: In the OPTIMIZE trial, we randomly assign elderly KTRs to an immunosuppressive regimen with standard-exposure calcineurin inhibitor (CNI), mycophenolate mofetil, and prednisolone or an adapted regimen with low dose CNI, everolimus, and prednisolone. In this substudy, we measured the humoral response after 2 (N = 32) and 3 (N = 22) COVID-19 mRNA vaccinations and the cellular response (N = 15) after 2 vaccinations. Results: . The seroconversion rates of elderly KTRs on a standard immunosuppressive regimen were only 13% and 38% after 2 and 3 vaccinations, respectively, whereas the response rates of KTRs on the everolimus regimen were significantly higher at 56% ( P = 0.009) and 100% ( P = 0.006). Levels of severe acute respiratory syndrome coronaVirus 2 IgG antibodies were significantly higher at both time points in the everolimus group ( P = 0.004 and P < 0.001). There were no differences in cellular response after vaccination. Conclusions: An immunosuppressive regimen without mycophenolate mofetil, a lower CNI dose, and usage of everolimus is associated with a higher humoral response rate after COVID-19 vaccination in elderly KTRs after transplantation. This encouraging finding should be investigated in larger cohorts, including transplant recipients of all ages. Abstract :